Survival rates of black sea turbot (Psetta maxima maeotica, L. 1758) broodstock captured by gill nets from different depths and their adaptation culture conditions - Samsun, N; Basaran, F (Kluwer Academic Publ, 2004)
WOS: 000222942600005 A study was performed during Spring 2002 to determine the survival rates of Black Sea Turbot (Psetta maxima maeotica) broodstock captured by gill nets from different depths (less than or equal to 20 m, 20-45 m, and greater than or equal to45 m) in Sinop Bay ( Black Sea, Turkey) and their adaptation to culture conditions. The weight of captured females ranged between 1.6 and 5.5 kg, while males ranged between 1.1 and 3.7 kg. Within 23 h of capture the fish were transported to C, anakkale ( Marmara Sea, Turkey). During transportation, the stocking density ranged from 19 to 40 kg/m(3) and no mortality was recorded. At the end of the fishing operations, the survival rates were calculated for Group 1 (less than or equal to 20 m), Group 2 (20-45 m), and Group 3 (greater than or equal to45 m) as 24.9, 71.4, and 92%, respectively. There were significant differences (p 0.05) between the survival rates of the groups. Eggs and sperms were obtained by hand-stripping. The mean fertilisation rate of the eggs was 3.19%. This low fertilisation rate was due to overripened eggs. At the end of adaptation period of 1 month, the survival rates of the broodstock were found to be 14.2, 45.4, and 48.3% for Groups 1, 2, and 3, respectively. No significant difference was found between the survival rates of the broodfish during the adaptation period (p > 0.05).